Optimal condition confirmation of treatment conditions through analysis of intratumoral apoptotic temperature range of microwave ablation for various microwave frequencies and antenna insertion depth - Kim, Donghyuk; Kim, Hyunjung (Science Progress, 2024)
Microwave ablation is a therapeutic technique that kills tumors by inducing heat generation in biological tissue through microwave emissions. Microwave ablation is a minimally invasive treatment technique, which has the advantage of treating deeply located tumors with less bleeding than traditional surgical techniques. In this study, the therapeutic effect of microwave ablation was analyzed from the perspective of the temperature range where apoptosis and necrosis occur. Through the numerical modelling, the tumor located inside the liver tissue was implemented, and the temperature distribution in the hepatic tissue was calculated by varying value of the microwave frequency, microwave antenna input power, and the insertion depth of the microwave coaxial antenna. Microwave frequencies were selected as 915, and 2450 MHz, and the insertion depth of the microwave coaxial antenna was set at a distance difference between the tumor tip and the slot of 4 to 16 mm. In addition, the microwave antenna input power was set to a range of 0 to 60 W. Based on the obtained temperature distribution, the apoptotic variables, which are parameters specifically defined apoptosis ratios that can quantitatively verify the therapeutic effect, were calculated to derive the microwave ablation treatment condition that maximizes the therapeutic effect for each microwave frequency. Through the quantitative analysis of apoptotic variables, the optimal conditions for maximum therapeutic effect were derived for each microwave frequency analyzed in this study. For frequencies of 915 MHz, the optimal insertion depth of the antenna is 8 mm above the bottom of the tumor, and the optimal microwave input power is 40 W. For 2450 MHz, the optimal insertion depth and input power were found to be 4 mm and 4 W, respectively. Ultimately, it is expected that the results presented in this study will lead to more improved treatment of microwave ablation in practice.
Keywords: Ablation Techniques; Apoptosis; Humans; Liver; Liver Neoplasms; Microwaves; Temperature; Apoptosis; coaxial-slot antenna; insertion depth; microwave ablation; microwave frequency; thermal damage